The Effect of Peak Signal to Noise Ratio (PSNR) Values on Object Detection Accuracy in Viola Jones Method - Sajati, Haruno (Institut Teknologi Dirgantara Adisutjipto, 2018)
Image quality is an important parameter in object detection. Image with good quality will produce high accuracy in the object detection process. Image quality is measured using the peak signal comparison of the original image with the interference that occurs in the image. This comparison is formulated with the Peak Signal To Noise Ratio (PSNR). PSNR values obtained from variations in image quality improvements will be seen in its characteristics in object detection methods using the Viola Jones method. The higher PSNR value will definitely produce better accuracy, but improving the image to the best quality will drain resources and a high computational burden so it needs to find a minimum PSNR value that can still be considered good in the object detection process. The minimum PSNR value for the image is said to be feasible to be processed 19.05 dB. The minimum PSNR value before the object can no longer be detected is 12.43 dB.